Enoxaparin Utilization Evaluation and Its Clinical and Laboratory Outcomes in Pediatric Patients in a Children's Teaching Hospital - Uldooz Samadi Bahrami; Alieh Safari Sharari; Hadis Pourkarami; Toktam Faghihi (Research Center for Rational Use of Drugs (RCRUD), 2020)
Backgrounds: In recent years, low molecular weight heparin use has increased in children. Dose of enoxaparin to achieve target anti-Xa and time to achieve anti-Xa are evolving and efficacy outcome data in terms of laboratory and clinical response rate in children still remains to be elucidated. Thus, in this drug utilization and evaluation study, we assessed patterns of enoxaparin use, its concordance with guidelines and laboratory and clinical outcomes in pediatric patients in a Children's teaching hospital.   Methods: In a prospective observational study, all pediatric patients with a thrombotic event who underwent treatment with enoxaparin were included. Demographic data, clinical outcome data based on follow-up sonography results, laboratory response based on anti-Xa and concordance with guidelines in terms of initial daily dose, duration of treatment, performing sonography to evaluate response, anti Xa check and time of anti-Xa check were evaluated. Results: During a 9-month period, 41 pediatric patients suffered a thrombotic event and received enoxaparin. Median age of participants was 18.5 months. The anti-Xa level became therapeutic on mean day 4.7 with a mean enoxaparin dose of 1.24 mg/kg. Among participants 42% achieved therapeutic anti-Xa with initial empirical dosing. Less than 25 % of participants had a follow-up sonography and among them, 77% demonstrated complete thrombosis resolution after 4-6 weeks of enoxaparin therapy. We observed one major bleeding event. Concordance with guidelines was low in the aspects of duration of treatment, performing sonography to evaluate response and anti-Xa check. Conclusion: With initial empiric dosing, it may take several days before anti-Xa become therapeutic. Among half of the children, a higher than recommended 1 mg/kg dose was required to achieve therapeutic anti-Xa level. Educational processes are mandatory regarding enoxaparin use and monitoring among clinicians to improve concordance with guidelines.